دور البيئة اللغوية في مهارة الكلام لدى الطلبة الجدد من الصف الأول بمعهد المدينة الحديث كارياتاني لامبونج الشرقية - Fadhilah Hanjani Putri; Sulthan Syahril; Erni Zuliana; Asti Fauziah (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The reason for choosing this title is to find out how the Role of Bi'ah Lughowiyyah in improving the ability of Maharah Al-Kalam in New students of class 1 MTS, at the same time this research is expected to provide new insights into the environmental conditions in the Modern Islamic Boarding School of Madinah in implementing the role of Bi'ah Lughowiyah and knowing what are the obstacles and challenges for new students in implementing the mandatory language regulations in the Islamic Boarding School environment. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation, continued with empirical techniques through data reduction, data presentation and data verification and ending with data validity checking techniques. The involvement of this research is to direct it to an environment that aims for students to play an active role in foreign language activities in communicating with all residents at the Islamic Boarding School in daily activities. The results of this study indicate that the results of its implementation at the Islamic Boarding School, the role of Bi'ah Lughowiyah towards Maharah Al-Kalam in the first grade students of MTS is quite effective. The implementation of Bi'ah Lughowiyah is divided into two weeks using Arabic then the next two weeks using English and so on, so that the implementation of Bi'ah Lughowiyah in the Islamic Boarding School environment becomes more organized. For those who do not use a foreign language in the Islamic Boarding School environment, they will be punished according to their respective criteria. Thus, it can be concluded that Bi'ah Lughowiyah has a very significant role in forming and improving the Maharah Al-Kalam of new students. The implications of this study emphasize that optimization of the language environment in Islamic Boarding Schools must continue to be carried out so that Arabic language learning is more effective and sustainable.